Management, Outcome, Risk, and Expectation Classification for Structural Fetal Anomalies to Aid Antenatal Counseling: A Systematic Review - Prabudh Goel; Vikesh Agrawal; Ramesh Babu Srinivasan (Wolters Kluwer Medknow Publications, 2024)
The aim of this study was to propose Management, Outcome, Risk, and Expectation (MORE) as a risk based stratification to aid in antenatal parental counseling and decision making through a systematic review of published literature. A Preferred Reporting Items for Systematic Reviews and Meta Analyses compliant systematic review was conducted to include articles that covered antenatal counseling of pediatric surgical conditions. The following information was solicited for each anomaly: primary organ syste*-m of involvement, single or multi system anomaly, natural history of the disease, standard management of the anomaly, need for antenatal intervention, and whether the anomaly requires any alteration in the obstetric management. Twenty two studies were identified fulfilling the inclusion criteria, between 1993 and 2023. Only two studies were found to have GRADE A recommendation and Level I evidence. Most of the studies were review articles/ survey, and 6 studies were found to be retrospective observational studies. Based on the analysis of the solicited information, the anomalies were stratified into a group subsequently maturing them into a simplified MORE classification scheme which stressed the importance of Management (10, 45.45%), Outcome (9, 40.90%), Risk (9, 40.90%), and Expectation (10, 45.45%) categories during antenatal counseling. MORE classification of fetal structural anomalies is a simple but comprehensive framework to assist the physicians and other medical personnel antenatal parental counseling and decision making.